Evidence-Based Case Report: A Case Series on the Use of Compression Dressing in Post-Total Laryngectomy Pharyngocutaneous Fistula - Histawara Subroto; Oke Kadarullah (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2026)
Pharyngocutaneous fistula (PCF) is among the most troublesome complications after total laryngectomy (TL), being the cause of substantial postoperative morbidity and prolonged hospitalization. The purpose of this study is to assess the clinical benefit of conservative management with compression dressing in patients who developed PCF following TL. Methods: This case series was performed via an evidence-based strategy based upon the PICO framework. Structured literature search using PubMed, Cochrane Library, and Google Scholar to identify pertinent studies that support the intervention. Our three patients with post-TL PCF, two of whom obtained complete fistula closure through compression dressing alone. No complications related to treatment were observed; clinical improvement and increased quality of life were apparent. Evidence from the existing literature, while limited, corresponds with these findings. We propose that compression dressing is an effective, cheap, and feasible conservative option for the management of PCF after TL, especially in a resource-limited environment.